Improving Marketing and Operational Efficiency in PT Rumekar Agribusiness through an Integrated E-Commerce based on a Design Thinking Approach - Donny Octariyanto; Magdalena A. Ineke Pakereng (SISTEMASI, 2026)
The advancement of information technology has driven the need for digital transformation across various sectors, including the agribusiness industry. PT Rumekar currently faces several operational challenges due to the continued use of conventional methods, including manual stock recording, fragmented financial data reporting, slow information flows, and limited marketing reach. This study aims to design an integrated web-based agribusiness e-commerce information system for PT Rumekar to address these challenges. The novelty of this study lies in integrating a sales module (digital storefront) with real-time inventory management and financial reporting within a single platform specifically tailored to agribusiness workflows. The system was designed using the Design Thinking methodology, which adopts a user-centered approach through five iterative stages: Empathize, Define, Ideate, Prototype, and Test. The system was developed using the Laravel framework and provides interfaces and functional features tailored to customers (users) and system administrators (admins). System testing was conducted using two approaches: Black Box Testing to evaluate system functionality and the System Usability Scale (SUS), involving five respondents consisting of three users and two system administrators to assess usability. The Black Box Testing results indicate that all system features functioned as designed and met the specified requirements. Meanwhile, the SUS evaluation yielded scores of 78.0 from users and 78.5 from administrators. Both scores correspond to Grade B and fall within the “Acceptable” acceptability range. These findings indicate that the Rumekar e-commerce website is feasible as a solution for improving sales efficiency, report management, and information dissemination. The system also has potential for adoption by other agribusiness companies facing similar operational challenges.